The Paradox of Policing and Security in a Globalised Context: Policing Dissent in Kashmir - Wang, Yazhuo (International Journal of Social Sciences and Public Administration, 2026)
Public order policing occupies a contested position within contemporary policing practices, often oscillating between the demands of maintaining public security and protecting civil liberties. This research examines the dynamics of public order policing through the case of Kashmir following the revocation of Article 370 in 2019. It focuses on two key policing strategies employed in response to widespread protests: the escalation of force against demonstrators and the prolonged shutdown of internet and media communications. Drawing on securitization theory and James Der Derian’s concept of “virtuous war,” the article argues that globalization contributes to the construction of a security discourse that legitimizes expanded police powers. Through the process of securitization, political dissent in Kashmir was reframed as a national security threat, thereby justifying exceptional policing measures. At the same time, the implementation of internet shutdowns reflects an attempt to contain the global circulation of information and limit transnational engagement with local protests. The case therefore illustrates the paradoxical relationship between globalization and policing: while global security discourse expands the scope of police authority, policing practices may simultaneously seek to restrict global information flows in the name of security.